KECEPATAN EFEKTIF MEMINDAI KAMUS BAHASA INDONESIA SISWA KELAS VII SMP NEGERI 1 PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Hendri Hendri; Elmustian Rahman; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study entitled Effective Speed Scanning Indonesian Dictionary Seventh Grade Students of SMP Negeri 1 Pagaran Tapah Darussalam Rokan Hulu. This study aims to determine the level of effective scan speed of large Indonesian dictionary and to determine significant differences between the class A and B class VII SMP Negeri 1 Pagaran Tapah Darussalam Rokan Hulu. The method used is descriptive analysis method with qualitative approach. Data of this study is the result of effective scan speed test large Indonesian dictionary given to students of class VII SMP Negeri 1 Pagaran Tapah Darussalam Rokan Hulu, which consists of two classes, with a population of 56 and the number of samples 56. The results effective speed scanning large dictionary Indonesian in the first test aspects of assessment indicators page, column, and row.the average value of 25,86 with the moderate category and the effective speed of scanning large dictionary Indonesian second test aspects of assessment indicators page, column, and row. get the average value of 27.79 by the middle category.Keywords: effective speed scanning large Indonesian dictionary.